Comparison of incentive, training conditions and motivation of female and male futsal athletes in teams from Paraná in Vale do Ivaí (Research, Society and Development, 2022)
The present study aimed to compare the incentive, training conditions and motivational aspects of female and male futsal practitioners in the Vale do Ivaí region of the state of Paraná. The research was characterized as a qualitative and quantitative study and was composed of a sample of 16 athletes belonging to the under-15 and under-17 categories of 8 teams (4 female teams and 4 male teams) from the region of Vale do Ivaí, in addition to 6 coaches of the respective teams. The teams from the cities of Arapuã, Ivaiporã, Manoel Ribas and Jardim Alegre took part in the research. As instruments, a structured interview prepared by the researchers was used to investigate the training conditions and to assess the levels of motivation, the Sports Motivation Scale (SMS-2) was used. Data were collected individually with each participant (interviews and completion of the questionnaire. For data analysis, the distribution of relative and absolute frequencies was used to categorize the answers of the interviews, and, for quantitative data, the Shapiro-Shapiro test was used. Wilk and t test for independent samples, p